Catching the missing million: experiences in enhancing TB & DR-TB detection by providing upfront Xpert MTB/RIF testing for people living with HIV in India. - Neeraj Raizada; Kuldeep Singh Sachdeva; Achuthan Sreenivas; Shubhangi Kulsange; Radhey Shyam Gupta; Rahul Thakur; Puneet Dewan; Catharina Boehme; Chinnambedu Nainarappan Paramsivan (PLoS ONE)
Background A critical challenge in providing TB care to People Living with HIV (PLHIV) is establishing an accurate bacteriological diagnosis. Xpert MTB/RIF, a highly sensitive and specific rapid tool, offers a promising solution in addressing these challenges. This study presents results from PLHIV taking part in a large demonstration study across India wherein upfront Xpert MTB/RIF testing was offered to all presumptive PTB cases in public health facilities. Method The study covered a population of 8.8 million across 18 sub-district level tuberculosis units (TU), with one Xpert MTB/RIF platform established at each TU. All HIV-infected patients suspected of TB (both TB and Drug Resistant TB (DR-TB)) accessing public health facilities in study area were prospectively enrolled and provided upfront Xpert MTB/RIF testing. Result 2,787 HIV-infected presumptive pulmonary TB cases were enrolled and 867 (31.1%, 95% Confidence Interval (CI) 29.4‒32.8) HIV-infected TB cases were diagnosed under the study. Overall 27.6% (CI 25.9-29.3) of HIV-infected presumptive PTB cases were positive by Xpert MTB/RIF, compared with 12.9% (CI 11.6-14.1) who had positive sputum smears. Upfront Xpert MTB/RIF testing of presumptive PTB and DR-TB cases resulted in diagnosis of 73 (9.5%, CI 7.6‒11.8) and 16 (11.2%, CI 6.7‒17.1) rifampicin resistance cases, respectively. Positive predictive value (PPV) for rifampicin resistance detection was high 97.7% (CI 89.3‒99.8), with no significant difference with or without prior history of TB treatment. Conclusion The study results strongly demonstrate limitations of using smear microscopy for TB diagnosis in PLHIV, leading to low TB and DR-TB detection which can potentially lead to either delayed or sub-optimal TB treatment. Our findings demonstrate the usefulness and feasibility of addressing this diagnostic gap with upfront of Xpert MTB/RIF testing, leading to overall strengthening of care and support package for PLHIV.